"ECOLOGIZATION" OF THE COURSE "THE TECHNIQUES FOR HOUSEHOLD ACTIVITIES" IN THE FRAMEWORK OF EDUCATIONAL PROGRAM FOR THE TEACHER OF TECHNOLOGY - Olena Lykholat (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article deals with different problems and issues in the general sphere of "ecologization" in the framework of educational course "Techniques for the household activities" in the system of professional preparation of future teacher of technology, with the specialization "Basics of the household activities". The core features and principles of the necessity of general "ecologization" in the field of education as an important part of the process of education system modernization in our country have been analyzed. In addition, the basics for the establishment of the new paradigm "human-nature-society" have been proposed. The algorithm for "ecologization" of the academic course "Techniques for the household activities" has been devised in the context of continuous development, rational natural resources use and environment protection. The general content of the educational program of the course, including the analysis of contemporary problems in ecology, based on the theoretical concepts, such as "household" and "household activities"has been revealed.